Wind speed, sun exposure and water status alter sunburn susceptibility of grape berries - Müller, Kai; Keller, Markus; Stoll, Manfred; Friedel, Matthias (Frontiers in Plant Science, 2023)
In the context of climate change, yield and quality losses from sunburn necrosis are challenging grape growers around the world. In a previous review (Gambetta et al., 2021), we identified several open questions that still prevent a comprehensive understanding of the complex interaction of genotype × phenology × environment leading to sunburn formation. In this paper we present results addressing some of these knowledge gaps. We examined the effects of wind speed on fruit surface temperature and the appearance of sunburn necrosis symptoms. The influence of the duration of heat exposure of berries was demonstrated. Riesling grapevines growing in an arid climate were fully irrigated or drought stressed, and clusters were exposed to sunlight by fruit-zone leaf removal (defoliation) at two developmental stages to examine the effect of acclimation on sunburn susceptibility. Sunburn symptoms were induced using infrared heaters while fruit surface temperature was measured using thermal imaging enabling the establishment of threshold temperatures (LT50). Higher wind speeds led to lower cluster temperatures and reduced sunburn severity. Longer durations of heat exposure required lower fruit surface temperatures to induce damage, while the differences in temperature after 60 min and 90 min of exposure were marginal (47.82 ± 0.25 °C and 47.06 ± 0.26 °C). Clusters of vines grown under water deficit were less susceptible to sunburn compared to those of well-irrigated plants following defoliation. The timing of defoliation did not affect the susceptibility of clusters within the irrigation treatments, but clusters were more resilient at the phenological stage of lag phase (EL-33) compared to the earlier pea-size (EL-31) stage.